Additive value of diffusion‐weighted MRI in the I‐SPY 2 TRIAL. Issue 6 (26th April 2019) - Li, Wen; Newitt, David C.; Wilmes, Lisa J.; Jones, Ella F.; Arasu, Vignesh; Gibbs, Jessica; La Yun, Bo; Li, Elizabeth; Partridge, Savannah C.; Kornak, John; ,; Esserman, Laura J.; et al.
Abstract : Background: The change in apparent diffusion coefficient (ADC) measured from diffusion‐weighted imaging (DWI) has been shown to be predictive of pathologic complete response (pCR) for patients with locally invasive breast cancer undergoing neoadjuvant chemotherapy. Purpose: To investigate the additive value of tumor ADC in a multicenter clinical trial setting. Study Type: Retrospective analysis of multicenter prospective data. Population: In all, 415 patients who enrolled in the I‐SPY 2 TRIAL from 2010 to 2014 were included. Field Strength/Sequence: 1.5T or 3T MRI system using a fat‐suppressed single‐shot echo planar imaging sequence with b‐values of 0 and 800 s/mm2 for DWI, followed by a T1‐weighted sequence for dynamic contrast‐enhanced MRI (DCE‐MRI) performed at pre‐NAC (T0), after 3 weeks of NAC (T1), mid‐NAC (T2), and post‐NAC (T3). Assessment: Functional tumor volume and tumor ADC were measured at each MRI exam; pCR measured at surgery was assessed as the binary outcome. Breast cancer subtype was defined by hormone receptor (HR) and human epidermal growth factor receptor 2 (HER2) status. Statistical Tests: A logistic regression model was used to evaluate associations between MRI predictors with pCR. The cross‐validated area under the curve (AUC) was calculated to assess the predictive performance of the model with and without ADC. Results: In all, 354 patients (128 HR+/HER2–, 60 HR+/HER2+, 34 HR–/HER2+, 132 HR–/HER2–) were included in the analysis. In the full cohort, adding ADC predictors increased the AUC from 0.76 to 0.78 at mid‐NAC and from 0.76 to 0.81 at post‐NAC. In HR/HER2 subtypes, the AUC increased from 0.52 to 0.65 at pre‐NAC for HR+/HER2–, from 0.67 to 0.73 at mid‐NAC and from 0.72 to 0.76 at post‐NAC for HR+/HER2+, from 0.71 to 0.81 at post‐NAC for triple negatives. Data Conclusion: The addition of ADC to standard functional tumor volume MRI showed improvement in the prediction of treatment response in HR+ and triple‐negative breast cancer. Level of Evidence: 2 Technical Efficacy Stage: 4 J. Magn. Reson. Imaging 2019;50:1742–1753.